A new species of Leptopus (Heteroptera: Leptopodidae) from caves in Iran, with notes on other cavernicolous Iranian Heteroptera - Khazaei, Zohreh; Polhemus, Dan A.; Tahami, Mohadeseh S. (Zootaxa, 2020)
The new species Leptopus gakalae is described from caves in Iran and compared to congeners occurring in the western Palearctic region. Figures are provided of the dorsal habitus and diagnostic morphological characters. Also provided are additional records for other species of Leptopus Latrielle, 1809, occurring from India westward through Europe and North Africa, as well as the first North American record of Leptopus marmoratus (Goeze, 1778) based on an agricultural quarantine intercept. A key is provided to all species of Leptopus occurring in the Western Palearctic region. Notes are also provided on other species of Heteroptera occurring in Iranian caves, with special reference to the small water strider Velia affinis Kolenati, 1857.